'Feeling disconnected' – risk factors for PGD and themes in grief counselling during the COVID-19 pandemic. A mixed-method study. Issue 1 (31st December 2023) - Hanauer, Christina; Telaar, Berit; Al-Dawaf, Nadja; Rosner, Rita; Doering, Bettina K.
ABSTRACT: Background: Due to its high death toll and measures to curb the pandemic, COVID-19 has affected grieving experiences and may contribute to risk factors for Prolonged Grief Disorder (PGD). Persons at risk for PGD often seek support from grief counselling. Objective: To explore whether pandemic-associated risk factors have become more important topics in counselling in a mixed-method design. Method: German grief counsellors ( n  = 93) rated whether pre-defined risk factors had become more important in grief counselling and indicated additional important themes in an open format. Results: The counsellors indicated that all pre-defined risk factors had become more important, though differing significantly in their frequency. Most frequently endorsed risk factors were lack of social support, limited possibilities to accompany a dying loved one and absence of traditional grief rituals. Qualitative analysis identified three additional themes: the societal impact of the pandemic, its impact on bereavement support and health care, and a chance for personal growth. Conclusions: The pandemic has affected bereavement experiences and grief counselling. Counsellors should monitor grief processes and specific risk factors to provide the best possible care for bereaved people when needed. HIGHLIGHTS: Pandemic-associated risk factors for PGD have become more important topics in grief counselling during COVID-19. Risk factors include especially a lack of social support, limited possibility to accompany a dying significant other and absence of traditional grief rituals. Future research is needed to investigate whether monitoring and addressing these risk factors can improve bereavement care.